The Influence Of Mother Tongue (Torajan Language) Toward Pronunciation Of English By The Eleventh Grade Students Of SMAN 1 Rantepao. - Aris Kaban Sendana (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
The objectives of this research is to find out the influence of mother tongue (Torajan Language) toward pronunciation of English by the eleventh grade students of SMAN 1 Rantepao.In analyzing the data of this reserach, the reseacrher employed qualitative method. The subjects of this research were the students of the eleventh grade students of SMAN 1 Rantepao. The data of this research were collected by making voice recording, observation and interview. The obtained data were analyzed in three major phases, namely reduction, data display and conclusion. The result of the research revealed some facts of the influence of mother tongue (Torajan language) toward pronunciation of English by the eleventh grade students of SMAN 1 Rantepao. First, the influence of mother tongue (Torajan language) of the sound /e/ that pronounced by the CIBI students. Such as, the pronunciation of letter “a” become /e/, the pronunciation of letter “i” become /e/, the pronunciation of letter “d” become /de/, the pronunciation of letter “ia” become /e/, the pronunciation of letter “io” become /e/, the pronunciation of letter “au” become /e/, the pronunciation of letter “ou” become /e/ and the pronunciation of letter “e” become /e/. Second, the types of the influence of mother tongue (Torajan language) that students pronounced by the eleventh garade students of SMAN 1 Rantepao (CIBI class) is the sound /r/follow the language style of Torajan people. Therefore, based on the research, the researcher conclude that there is influence of mother tongue (Torajan language) toward pronunciation of English by the eleventh grade students of SMAN 1 Rantepao in pronouncing the sound /e/ and /r/.